The Interplay of Culture and Compensation: How Financial Rewards Impact Engagement in the Public Sector? - Dickson Mdhlalose (Jurnal Ilmiah Manajemen dan Bisnis, 2026)
Cultural research on the influence of individuality and collectivism on employee engagement is lacking. This study aims to analyse the impact of employee financial rewards on employee engagement, focusing on individualistic and collectivistic cultures as moderating variables in a public sector organisation. This research employed standardised face-to-face open-ended interviews. The research instrument is made from one theme and five open-ended questions to address the objectives of this study. The constantcomparative dataanalysis approach was employed inconjunction with content analysis. The researcher categorised the data based on their disparities and similarities. This study found that the municipality offers its employees financial rewards; however, due to inequality, unfairness, favouritism, and political influence, employees are not rewarded fairly, leading to unhappiness and disengagement from their work and the organisation. The municipality does not practice either a collectivistic or individualistic culture. A poor imbalance between individualistic and collectivistic cultures reduces the impact of financial rewards on employee engagement. This study's findings emphasise that the effectiveness of monetaryrewardsonemployeeengagementdependsontheorganisation's practicesandtheequilibriumofindividualisticandcollectivisticcultures.